SKIN CARE FOR MENOPAUSAL WOMEN: A WEB SYSTEM - Harbindar Singh, Umeeta Kaur (IRC, 2019)
One of the major concerns that affect women when they go through menopause is the effects on their skin. Skin is the largest organ of a human body and therefore, the skin does have an impact on a person‟s appearance. Women going through menopause even through the early stages will have some effects on their skin as their skin gets drier with the appearance of wrinkles. In short, the ageing of the skin occurs. This is a project on implementing a web system or a web based guide in order for these women to browse through the information on handling their skin and performing their skin care routine daily that will help to improve their skin and appearance. Compare to younger women, older women between the ages of 40 to 50 and even above 50, must take more initiative and care for their skin more as the sensitivity of their skin becomes higher due to menopause. The web based guide that is implemented will be able to help these users to keep track of their skin care and they can also rely on the information displayed in the web.